Relational learning: Embedding Indigenous ways in whitestream social work - Hammond, Libby; Miller, Keith (The Australian Journal of Indigenous Education, 2023)
Social work globally acknowledges its need to decolonise its education to produce social workers who can work responsively alongside marginalised Indigenous peoples. Yet the problem is that universities have struggled to operationalise the integration of Indigenous ways of knowing, being and doing into social work education. Uniquely, this study explored relationships that impact on the integration of Indigenous content for academics in social work education. A qualitative approach was used, interviewing both Indigenous and non-Indigenous academics in Australia and Aotearoa/New Zealand. The outcome of the study produced a relational model for academics that focuses upon six key relationships an academic has: to self; with students; to Indigenous knowledges, languages and cultures; with peers; with those in power and the whitestream; with elders, kaumatuas and Indigenous communities. With the goal of decolonising social work education, this relational model provides insight into different ways that an academic may develop and embed their integration of Indigenous content into their teaching. This study offers a relational model that could promote curriculum change in social work, as well as in other disciplines beyond Australia and Aotearoa/New Zealand.